Gate Keeper Role in Building Network of Interreligious Figures Based Local Wisdom In Gresik - Setyo Budi Oetomo (Analisa: Journal of Social Science and Religion, 2015)
The composition of community in Gresik which is initially based on the traditional Islam has changed due to the development of non Muslim community and other Islamic sects. These phenomena might cause conflicts between religious followers. To reduce the potency of religious based conflicts, religious leaders use FKUB and FORMALINA as a communication network between believers. This is a qualitative research that concerns on the relationship patterns and the values within networks. Data was collected using FGD, in-depth interviews and document analysis. By analyzing the communication network between actors founded that the pattern of relationships between religious leader well established because there was the actor who played the gate keeper. The actor is capable of filtering information and liaison among actors in FKUB and in FORMALINA. Gate keeper is very crucial role in building mutual trust among actors interfaith. The religious leaders using local wisdom in establishing communication between religious leaders. The values of local wisdom has become a social character of the group.